ENHANCING PROBLEM-SOLVING AND COLLABORATION SKILLS THROUGH PROBLEM-BASED LEARNING (PBL) WITH COMPUTATIONAL THINKING (CT) IN DIGESTIVE SYSTEM FOR EIGHT GRADES - Utami, Rigen (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The low problem-solving skills and collaboration skills of Indonesian students, along with the demands of the 21st century skills, encourage the integration of Problem-Based Learning (PBL) with Computation Thinking (CT) approach as an innovative solution to train the ability to solve complex problems collaboratively. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model integrated with a Computational Thinking (CT) approach in enhancing students' problem- solving and collaboration skills. The research was motivated by students' low problem-solving skills (pre-cycle: 52%) and the need for innovative approaches that encourage 21st-century skills. This type of research is a Classroom Action Research with Kemmis & Mc Taggart spiral model, the study implemented two cycles. The research subjects consisted of 31 students of class VIII A in the 2023/2024 academic year. Data were collected through observation, questionnaires, and student worksheets (LKPD), then analyzed using descriptive quantitative-qualitative methods. The results revealed a significant improvement in: (1) problem-solving skills (N-gain = 0.83, high category) and (2) collaboration skills (N-gain = 0.91). All indicators of achievement were met in cycle II, prompting the cessation of further cycles. The PBL model that integrating with a CT approach effectively enhances problem- solving and collaboration skills. This study provides empirical evidence that the integration of CT into PBL model facilitates active learning and advances 21st-century skills